Assessing the Influence of Different Interest Groups on International Tax Policy: Evidence from the BEPS Project - Christina Elschner; Inga Hardeck (Contemporary Accounting Research, 2021)
This study investigates the influence of three interest groups—businesses, the tax profession, and civil society—on tax rules in the context of the Organisation for Economic Co-operation and Development (OECD) Base Erosion and Profit Shifting (BEPS) project. Our study is important as prior research has not examined the direct influence of various interest groups on the content of tax rules by means of comment letters. Using content analysis, we seek to explain the lobbying success of the different interest groups by examining the relevance of the kind of information transmitted and the alliance strategies used. Results indicate that lobbying success is mainly explained by the vested interests of the three groups, with businesses less successful than the other two interest groups as long as all interest groups are equally able to provide information. We also find that the lobbying success of businesses increases when proposals require specific expertise. However, bias is still relevant for lobbying success as we find that proposals from tax professionals with practical experience, likely to reflect less bias, are relatively more successful than proposals from businesses. Furthermore, our results suggest that mobilizing commenters who have a shared interest in the form of alliances is a promising lobbying strategy. Overall, our findings highlight the importance of expertise and collective actions for lobbying success.
Keywords: 650; aggressive tax planning; BEPS; comment letter; interest groups; tax lobbying; tax policy; planification fiscale agressive; BEPS; lettre d'observations; groupes d'intérêt; lobbying fiscal; politique fiscale